α′ corrections to KPV: an uplifting story - Schreyer, Simon; Venken, Gerben (Journal of high energy physics, 2023)
In earlier work, the effect of α′2 curvature corrections on the NS5-brane responsible for the decay of anti-D3-branes in the set-up of Kachru, Pearson, and Verlinde (KPV) was considered. We extend this analysis to include all known α′2 corrections to the action of an abelian fivebrane which involve not just curvature but also gauge fields and flux. We compute the value of these terms at the tip of the Klebanov-Strassler throat to obtain the α′2 corrected potential for the NS5-brane of KPV. The resulting potential provides a novel uplifting mechanism where one can obtain metastable vacua with an arbitrarily small positive uplifting potential by fine-tuning α′ corrections against the tree-level potential. This mechanism works for small warped throats, both in terms of size and contribution to the D3-tadpole, thereby sidestepping the issues associated with a standard deep warped throat uplift which are deadly in KKLT and, as we explicitly check, severely constraining in the Large Volume Scenario.
Veröffentlicht: 31. Juli 2023
Gesehen am 21.09.2023